Reynaldo Alarcón and the critical history of psychology in Peru - Arias Gallegos, Walter L. (2022)
The history of psychology is a discipline funded by the contributions of the sociology of knowledge, the history of science and epistemology. These contributions provide said discipline with a more critical orientation: a quality necessary for its objective development in the face of the social reality in which it takes place. In this article, we review the development of the historiography of psychology, its institutionalization and its diffusion in Latin America, and analyze the reception of the critical history of psychology in Peru through its historiography, its representatives and, mainly, through the work of Reynaldo Alarcón, one of the greatest exponents of this branch in our country. Authorship contributionThe authors participated in the entire development of the article.